2014
DOI: 10.1186/1465-9921-15-77
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of inhaled corticosteroids can be safe in COPD patients at low risk of exacerbation: a real-life study on the appropriateness of treatment in moderate COPD patients (OPTIMO)

Abstract: BackgroundIt has been suggested that withdrawal of inhaled corticosteroids (ICS) in COPD patients on maintenance treatment results in deterioration of symptoms, lung function and exacerbations. The aim of this real-life, prospective, multicentric study was to investigate whether withdrawal of ICS in COPD patients at low risk of exacerbation is linked to a deterioration in lung function and symptoms and to a higher frequency of exacerbations.Methods914 COPD patients, on maintenance therapy with bronchodilators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
13

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 31 publications
3
84
0
13
Order By: Relevance
“…All patients were also receiving an LABA and a long‐acting, muscarinic antagonist. The finding that withdrawal of ICS in COPD may not increase exacerbation rates has been replicated …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…All patients were also receiving an LABA and a long‐acting, muscarinic antagonist. The finding that withdrawal of ICS in COPD may not increase exacerbation rates has been replicated …”
Section: Discussionmentioning
confidence: 91%
“…The finding that withdrawal of ICS in COPD may not increase exacerbation rates has been replicated. 10,11 There is evidence that ICS may be harmful. Inhaled corticosteroids increase the risk of developing pneumonia in COPD.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…This requires further investigation. ICS back titration is now a focus of both asthma and COPD management following studies published in 2014 showing that ICS dose reduction in COPD was possible without an increase in exacerbations 83 84. Whether this is safe in asthma–COPD overlap remains to be determined.…”
Section: Future Researchmentioning
confidence: 99%
“…The number of patients overexposed to ICS may now increase, as many patients receiving high‐risk treatment would now be considered low risk and would not be indicated to use ICS . Fortunately, at least four studies of different designs have reported about the safety of ICS withdrawal among low‐risk patients . Taken together, the evidence suggests that ICS discontinuation is safe for current low‐risk patients.…”
Section: Step Down From Triple Therapy To Double Bronchodilationmentioning
confidence: 99%